Translation Quality Assessment of popular science material (on the material of the «National Geographic» article): Juliane House’s model - Aubakir, Nurken (Ye.A.Buketov Karaganda State University Publishing house, 2019)
The article presents analysis and translation quality assessment of world-famous popular science magazine National Geographic article translations into Kazakh language. The original materials in the American version of the magazine has been printed in English since 1888, but the translation into about forty different other languages of the world has been published in various countries only since 1995. The magazine has been published in Kazakhstan since 2016 in the state language. This article provides a brief overview of the translation quality assessment model of the German scholar Juliane House, as well as the definition of translation types. The author of the article attempts to analyze the quality of translation from English language to Kazakh language by comparing the original and the translated materials. While analyzing the quality of translation, structural analysis is carried out according to House’s model, namely, analysis of the source text, definition of the function, comparison of the original and translated materials, definition of quality and conclusion.
Ғылыми-танымал дискурстың аударма сапасын бағалау («National Geographic» мақаласының материалы негізінде): Джулиана Хаус моделі
Оценка качества перевода научно-популярного дискурса (на материале статьи «National Geographic»): модель Джулианы Хаус
Keywords: translation quality analysis; translation quality assessment; TQA model; National Geographic; popular science material; translation analysis; Kazakh language